TOWARD DEVELOPING AN INTELLIGENT PERSONAL ASSISTANT FOR TUNISIAN ARABIC - Inès Zribi; Lamia Hadrich Belguith (Jordanian Journal of Computers and Information Technology, 2022)
Intelligent systems powered by Artificial Intelligence techniques have been massively proposed to help humans in various tasks. The intelligent personal assistant (IPA) is one of these smart systems. In this paper, we present an attempt to create an IPA, that interacts with users via Tunisian Arabic (TA), (the colloquial form used in Tunisia). We propose and explore a simple-to-implement method for building the principal components of a TA IPA. We apply Deep learning techniques: CNN [1], RNN encoder-decoder [2] and end-to-end approaches for creating IPA speech components (Speech Recognition and Speech Synthesis). In addition, we explore the availability and free dialog platform for understanding and generating the suitable response in TA for a request. For this proposal, we create and use TA transcripts for generating the corresponding models. Evaluation results are acceptable for the first attempt. [JJCIT 2022; 8(4.000): 318-335]